2019
DOI: 10.11604/pamj.2019.33.236.15507
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with acute kidney injury recovery in a tertiary hospital in Ghana: a prospective study

Abstract: IntroductionAcute kidney injury (AKI) is a challenging problem in developing countries due to late presentation of its victims to health care facilities. Data on the pattern of AKI, its outcome and factors associated with its recovery is scanty in developing countries therefore impeding AKI management. Aim: to study AKI recovery rate and its associated factors.MethodsAn observational study conducted from September 2013 to June 2014 at Korle-Bu Teaching Hospital (KBTH). Participants were adults, admitted with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Interestingly, the severity of AKI was signi cantly associated with an increased likelihood of non-renal recovery. This is consistent with previous studies that demonstrated a signi cant association between the severity of AKI and incomplete recovery (19,29,30,34). Furthermore, declined renal function at hospital discharge and severity of AKI are found to be associated with the progression of AKI to CKD and mortality.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the severity of AKI was signi cantly associated with an increased likelihood of non-renal recovery. This is consistent with previous studies that demonstrated a signi cant association between the severity of AKI and incomplete recovery (19,29,30,34). Furthermore, declined renal function at hospital discharge and severity of AKI are found to be associated with the progression of AKI to CKD and mortality.…”
Section: Discussionsupporting
confidence: 92%
“…Acute Kidney Injury (AKI) is one of the most worrying complications in hospitalized patients, even in non-critical care units [ 1 ], due to its potential predisposition to unfavorable outcomes, such as chronicity of renal damage, lack of recovery, and mortality [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence of renal recovery and mortality in intensive care units [ 2 , 12 ], but in non-critical care, there are few studies that address this relationship; consequently, it is believed that a better understanding of this condition would allow for more consistent care and, therefore, for the optimization of effective, preventive and individualized strategies as a way to mitigate risk and improve the clinical outcomes of hospitalized patients with AKI.…”
Section: Introductionmentioning
confidence: 99%